Modifying soil bacterial communities in saline mudflats with organic acids and substrates - Liu, Xiaoyu; Zhong, Liang; Yang, Ruixue; Wang, Huiyan; Liu, Xinbao; Xue, Wei; Yang, He; Shen, Yixin; Li, Jianlong; Sun, Zhengguo (Frontiers in Microbiology, 2024)
In this paper, the effects of applying exogenous organic acids combined with biological substrate on the composition and diversity of soil bacterial community were studied in moderately saline mudflats in Jiangsu Province.Methods A combination of three exogenous organic acids (humic acid, fulvic acid, and citric acid) and four biological substrates (cottonseed hull, cow manure, grass charcoal, and pine needle) was set up set up on a coastal saline mudflat planted with a salt-tolerant forage grass, sweet sorghum. A total of 120 kg ha -1 of organic acids and 5000 kg ha -1 of substrates were used, plus two treatments, CK without application of organic acids and substrates and CK0 in bare ground, for a total of 14 treatments.No significant difference was found in the alpha diversity of soil bacterial community among all treatments (P ≥ 0.05), with the fulvic acid composite pine needle (FPN) treatment showing the largest increase in each index. The beta diversity differed significantly (P < 0.05) among all treatments, and the difference between citric acid-grass charcoal (CGC) and CK treatments was greater than that of other treatments. All treatments were effective in increasing the number of bacterial ASVs and affecting the structural composition of the community. Citric acid-cow manure (CCM), FPN, and CGC treatments were found to be beneficial for increasing the relative abundance of Proteobacteria, Chloroflexi, and Actinobacteria, respectively. By contrast, all treatments triggered a decrease in the relative abundance of Acidobacteria. Conclusions Among the 12 different combinations of exogenous organic acid composite biomass substrates applied to the coastal beach, the CGC treatment was more conducive to increasing the relative abundance of the salt-tolerant bacteria Proteobacteria, Chloroflexi and Actinobacteria, and improving the community structure of soil bacteria.The FPN treatment was more conducive to increase the species diversity of the soil bacterial community and adjust the species composition of the bacterial community.